Serum levels of soluble platelet endothelial cell adhesion molecule-1 and vascular cell adhesion molecule-1 are decreased in subjects with autism spectrum disorder - Kameno, Yosuke; Iwata, Keiko; Matsuzaki, Hideo; Miyachi, Taishi; Tsuchiya, Kenji J; Matsumoto, Kaori; Iwata, Yasuhide; Suzuki, Katsuaki; Nakamura, Kazuhiko; Maekawa, Masato; Tsujii, Masatsugu; Sugiyama, Toshirou; et al. (Molecular autism, 2013)
Adhesion molecules, such as platelet-endothelial adhesion molecule-1 (PECAM-1), platelet selectin (P-selectin), endothelial selectin (E-selectin), intracellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1), are localized on the membranes of activated platelets and leukocytes and on the vascular endothelium. Recently, we measured serum levels of soluble (s) forms of adhesion molecules in adults,18 to 26 years old, with autism spectrum disorder (ASD) and observed low levels of sPECAM-1 and sP-selectin. A subsequent study showed a similar result in children two to four years old with ASD. However, information about school age (five to seventeen years old) ASD subjects is required to determine whether adhesion molecules are also reduced in individuals with ASD in this age range. Twenty-two subjects with high-functioning ASD and 29 healthy age-matched controls were recruited. ELISA was used for sPECAM-1, and a suspension array system was used for sP-selectin, sE-selectin, sICAM-1 and sVCAM-1 measurements. We found that serum levels of sPECAM-1 (U = 91.0, P<0.0001 by Mann-Whitney U test) and sVCAM-1 (U = 168.0, P = 0.0042) were significantly lower in ASD subjects than in controls. Subsequently, we examined the correlations between serum levels of either sPECAM-1 or sVCAM-1 and clinical variables including Autism Diagnostic Interview - Revised subscores and our previous cytokine profile data from the same ASD subjects. However, we did not find any significant correlations between them. The present results, taken together with previous results, suggest that sPECAM-1 may play a role in the generation and development of ASD, beginning in childhood and lasting until adulthood.